Characterization of a wheat mutant missing low-molecular-weight glutenin subunits encoded by the B-genome. (January 2017) - Lee, Jong-Yeol; Kang, Chon-Sik; Beom, Hye-Rang; Jang, You-Ran; Altenbach, Susan B.; Lim, Sun-Hyung; Kim, Young-Mi; Park, Chul-Soo
Abstract: DH20, a new wheat mutant missing low-molecular weight glutenin subunits encoded by the Glu-B3 locus, was discovered among double haploid lines obtained from a cross between the Korean wheat cultivars Keumkang and Olgeuru. Absence of the Glu-B3 LMW-GS proteins was determined by one-dimensional gel electrophoresis (SDS-PAGE) and confirmed by two-dimensional gel electrophoresis (2-DGE) and tandem mass spectrometry (MS/MS). The deletion of Glu-B3 genes was also demonstrated using allele specific DNA markers. Basic agronomic traits, protein content, dough mixing properties and bread loaf volume of DH20 and parental wheat cultivars were evaluated in field-grown wheat over a two year period. This mutant is a valuable resource for understanding the function of individual LMW-GS alleles or genes at the Glu-B3 locus using either breeding or biotechnology approaches. Highlights: A new wheat mutant missing Glu-B3 LMW-GS proteins was discovered. Absence of Glu-B3 LMW-GS proteins was determined by SDS-PAGE, 2-DGE and MS/MS. This mutant is a valuable resource for understanding the function of individual LMW-GS alleles or genes at the Glu-B3 locus.